Resolusi Konflik Agama Berdasarkan Budaya Penginyongan Di Kabupaten Banyumas - Muh Bachrul Ulum; Pangestika Rizki Utami (LPPM UIN Saizu Purwokerto, 2022)
Conflict resolution is a process of analysis and problem solving that considers individual and group needs such as identity and recognition of the institutional changes needed to meet the needs of the world. The application of local wisdom values ​​as a cultural approach in resolving conflicts is the best and most effective approach without resorting to repressive measures. Researchers argue that religious harmony is an obligation for regions with heterogeneous populations with various backgrounds. One form of settlement in dealing with and resolving religious conflicts is through a cultural approach that grows and develops in society as part of local wisdom. The research used in this research is field research, in the process of this research the researcher interviewed the management of the Religious Communication Forum and interfaith leaders with Banyumas culture and the Banyumas Ministry of Religion office. Banyumas people with a Penginyongan cultural background can be directed to become a means of resolving religious conflicts. Harmonization of the culture of the Banyumas people which is interpreted through the life of the Banyumas indigenous people. The uniqueness of Banyumas culture which is built with the concept of the culture of penginyongan and the character of cablaka has a good impact on solving a problem. Cablaka is a way for the people of Banyumas to convey something without being direct, which means conveying what is. Cablaka culture plays a role in building a communication network in the Banyumas community. Potential conflicts that arise both in religious life and society in general can be anticipated with cultural communication. Keywords: Conflict Resolution, Religious Conflict, Penginyongan Culture